Propuesta para la creación del Consultorio Empresarial UAN: caso clúster “cuero, calzado y marroquinería” del sector Restrepo (2024)
This degree work presents a proposal for the establishment of a business consulting office for the leather, footwear, and leather goods cluster in the Restrepo sector, Bogota. The objective is to conduct a diagnostic study as a basis for the creation of a business consulting office accessible to the primary sector of influence of the Universidad Antonio Nariño that provides advisory and consulting services, especially for MSMEs of the cluster. The current situation of the sector was analyzed, identifying problems and opportunities, measuring the impact of the proposal.